2014
DOI: 10.1063/1.4903848
|View full text |Cite
|
Sign up to set email alerts
|

Oblique ion-acoustic cnoidal waves in two temperature superthermal electrons magnetized plasma

Abstract: A study is presented for the oblique propagation of ion acoustic cnoidal waves in a magnetized plasma consisting of cold ions and two temperature superthermal electrons modelled by kappa-type distributions. Using the reductive perturbation method, the nonlinear Korteweg de-Vries equation is derived, which further gives the solutions with a special type of cnoidal elliptical functions. Both compressive and rarefactive structures are found for these cnoidal waves. Nonlinear periodic cnoidal waves are explained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…Integrating the Kappa distribution over velocity space, the number density for electrons can be obtained as (Panwar et al 2014)…”
Section: Basic Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating the Kappa distribution over velocity space, the number density for electrons can be obtained as (Panwar et al 2014)…”
Section: Basic Equationsmentioning
confidence: 99%
“…Both compressive and rarefactive solitary structures have been observed in two temperature electron plasmas. Lastly, Panwar et al (2014) studied the oblique propagation of ion acoustic cnoidal waves in magnetized plasma consisting of cold ions and two temperature superthermal electrons modeled by kappa-type distributions. They found that the density ratio of hot electrons to ions significantly modifies compressive/refractive wave structures.…”
Section: Introductionmentioning
confidence: 99%
“…(17) and (18) in Eqs. (11)(12)(13)(14)(15)(16) and collecting the lowest order ∼ 3/2 terms from continuity and x component of momentum equations of e-p plasmas, we obtain the following equations:…”
Section: Derivation Of Korteweg-de Vries (Kdv) Equationmentioning
confidence: 99%
“…In order to derive the KdV equation, we collect the next higher order terms from set of dynamic equations (11)(12)(13)(14)(15)(16). The next higher order ∼ 5/2 terms of continuity equations, x -component of momenta equations, Faraday's and Ampere's laws are respectively described as below:…”
Section: Derivation Of Korteweg-de Vries (Kdv) Equationmentioning
confidence: 99%
See 1 more Smart Citation